Faktor Penentu Akuntabilitas Pengelolaan Dana Desa - Eny Wahyuningsih; Yolanda Pratami; Gilang Amrizal (Jurusan Akuntansi Fakultas Ekonomi Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2023)
Purpose: The research aims to find evidence of the influence of budget targets, competence of village apparatus, and leadership on the accountability of managing village funds in Bantan District, Bengkalis Regency.Method: This study uses a quantitative approach. The research data is primary data and secondary data. Data collection was carried out by giving questionnaires to all respondents in this study, namely 69 respondents. The analysis technique used is validity test, reliability test, normality test, tolerance and vif test, multiple linear regression test, t test and the coefficient of determination adj R2.Results: The results of this study can be concluded that Clarity of Budget Targets has an effect on Village Fund Management Accountability, Village Apparatus Competence has an effect on Village Fund Management Accountability and Leadership has an effect on Village Fund Management Accountability.Implications: This research can be taken into consideration especially for the Village Government in Bantan District to further clarify budget targets, improve village apparatus competence and good leadership because it will affect the level of accountability or accountability for managing village funds.Novelty: This research is a replication of previous research by replacing the village research object in Bantan District, Bengkalis Regency